2021
DOI: 10.3390/ijerph182312732
|View full text |Cite
|
Sign up to set email alerts
|

Sports Bra Preferences by Age and Impact of Breast Size on Physical Activity among American Females

Abstract: For many females, sports bras are an essential piece of equipment for participation in sports and physical activity. Breast pain or discomfort from lack of support may be a contributing factor to the noted gender disparity in physical activity of females compared to males. Our objective was to evaluate sports bra usage and characterize sports bra preferences of an active female cohort. This multicenter cross-sectional survey study was conducted at five geographically distinct academic centers. Our measure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 37 In addition, a study conducted on 438 women with a mean age of 22 ± 12.2 years from five states in the United States found that breast size prevented women from being physically active. 55 In the present study, women were from three Mexican states and had a similar age, and pain was reported regardless of breast size category. However, breast size was unrelated to PA levels, which also showed higher PA than a UK sample.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“… 37 In addition, a study conducted on 438 women with a mean age of 22 ± 12.2 years from five states in the United States found that breast size prevented women from being physically active. 55 In the present study, women were from three Mexican states and had a similar age, and pain was reported regardless of breast size category. However, breast size was unrelated to PA levels, which also showed higher PA than a UK sample.…”
Section: Discussionmentioning
confidence: 82%
“…Breast as a research subject related to exercise behavior has recently produced relevant reports, including important information regarding breast pain, breast as a barrier to PA, and bra characteristics in active and the general population. 24 , 34 , 38 , 53 55 Breast pain is associated with VPA in European women. 15 In this study, breast pain increased with the menstrual cycle and exercise; however, breast pain and health knowledge were unrelated to levels of PA.…”
Section: Discussionmentioning
confidence: 99%
“…Following title, abstract, and full text screening, 77 articles were eligible for inclusion in our review (Figure 1). 8,[10][11][12][13][14][16][17][18]20,21,26, Reasons for exclusion at the full text level are listed in Table S3, with the most frequent reason for exclusion being the article was not an original research study. S3 and S4 Detailed study information was extracted from the included articles and is listed in Table S3.…”
Section: Literature Aimed At Studying the Impact Of Breasts/bras On P...mentioning
confidence: 99%
“…Additionally, only one study reported the household income of participants. 17 Published studies largely took place in Australia, the United Kingdom, or the United States (n = 71, Figure 2C), and included studies mainly focused on nonathletes (n = 62, Figure 2D). Of those that did include athletes, runners were the most commonly studied population (n = 9/17, (two studies included both athletes and non-athletes) Figure 2D).…”
Section: Literature Aimed At Studying the Impact Of Breasts/bras On P...mentioning
confidence: 99%
See 1 more Smart Citation